Wykorzystanie metod eksploracyjnej analizy tekstu do identyfikacji kluczowych zagadnień zawartych w dużych zbiorach publikacji naukowych - Grabowski, Mariusz (Application of Text Mining Methodology to Identification of Key Issues Contained in Huge Sets of Scientific Publications, 2008)
The development of data storage and retrieval tools, observed over the last decade, resulted in the increase of data availability - the text documents in particular. This increased availability enables the detailed analysis of huge sets of documents. The paper presents the use of text mining methods to identify the key theoretical issues in management information systems field. As a research sample abstracts and keywords will be used from all research papers published over the 30-year period (1997-2006) in top ranking research paper of management information systems field - MIS Quarterly.
Prace Naukowe Uniwersytetu Ekonomicznego we Wrocławiu = Research Papers of Wrocław University of Economics; 2008; Nr 7, s. 256-263